PEKERJA ANAK DAN PENGHASILAN KELUARGA - Nazeli Andan (Jurnal Ekonomi Pembangunan, 2009)
This paper aims to analyze child labor and family income by taking a shoe shine case study in the city of Palembang. This paper aims to analyze child labor and family income by taking a case study in the city of Palembang. The sample in this study was a shoe shine kids. Data used in this study are primary data as the primary data. The data was collected by survey or observation to the location of the research or direct interviews with selected respondents in the sample and is equipped with a list of questions. In addition, the use of secondary data for the study of literature, a study presented earlier and others that originate from the reports, newspaper, journals or other sources. The data obtained are processed by the tabulation in one direction or the tabulation of frequencies and cross tabulation and describe qualitatively using the theory of relating in order to strengthen the analysis. Results of a study showed that the involvement of children in a job shining shoes because they want to helpÂ family finances. By working their lowest earning USD. 5.000, - and the highest Rp. 15.000,-/day. Faktor education does not affect the amount of revenue earned, nor hours of work is not a great influence on earnings, possibly affecting the number of people who want to shine shoes. Keywords: Child Labor, Family Income